Study on the Structural Strength Assessment of Mega Offshore Wind Turbine Tower - Jianlun Jiang; Han Koo Jeong; Haoyu Dou (Energies)
This study addresses the critical engineering challenges in the structural design of offshore wind turbine towers, focusing on enhancing resistance to extreme environmental loads. As the demand for renewable energy increases, the design of mega offshore wind turbines requires robust solutions for structural reliability and longevity. Using finite element analysis (FEA), this research evaluates the effectiveness of various internal stiffener designs—ring stiffeners, skeletal-type stiffeners, and their combinations—in reinforcing cylindrical offshore wind turbine towers against wind and wave forces. Detailed simulations model the physical behavior of different stiffener configurations, assessing parameters such as von Mises stress distributions, displacement and buckling under load. The results indicate that towers with combined stiffener designs exhibit superior structural resistance and reduced stress concentrations compared to those with singular stiffeners or none. These findings have significant implications for the design and construction of mega offshore wind turbines, highlighting the importance of integrating advanced stiffener configurations to improve structural stability in harsh marine environments.